Singularity - Valencia Sariputra (JURNAL RUPA, 2020)
We often find ornament on Indonesian traditional textile and fashion such as batik, songket, tenun, and some of them are natural dyed. However, most of the Indonesian teenagers in year 2019 do not wear traditional textile and fashion as their daily outfit, they just want to wear it on special events. Based on the information that already collected, in Jakarta Fashion Week 2019 there are only few designers used natural dye on their collection. Therefore, this research is to produce fashion with ornaments on silk fabric using natural dye based on singularity trend and as teenager’s style. The method used in this research is an exploratory research method carried out qualitatively and quantitative. The results of the research are in the form of ornamental kecakdance painted with secangextract on silk fabric, which was then sewn into clothing and designed based on teenagers’s style.